Real-time quantification of network growth of epoxy/diamine thermosets as a function of cure protocol - Andrew P. Janisse (Taylor & Francis Group, 2019)
Traditionally, understanding of thermoset cure has been limited to the analysis of a single degree of cure value obtained via techniques such as dynamic scanning calorimetry. Such analyses limit the scope of understanding of network development during cure. The continued development of rapid cure matrix chemistries necessitates the advancement of analytical techniques capable of quantifying how thermal cure profiles influence crosslinked network architectures throughout cure. In this work, the formation of epoxy/diamine networks was studied, in real time, throughout cure with Fourier Transform Infrared Spectroscopy in the near infrared region (NIR). The NIR technique allows for direct quantification of all functional groups directly involved in the cure of aerospace matrices. This work establishes a means to view a complete picture of the development of epoxy/diamine networks throughout cure, which allows for a more complete understanding of the effect of cure protocol on final network structure.